2017
DOI: 10.1177/1049909117711997
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Quality of Life at the End of Life: Interdisciplinary Team Perspectives

Abstract: This ethnographic study draws on the experiences of members of interdisciplinary care teams working with end-of-life care patients to identify strategies to improve quality of life through care practices. We surveyed 133 staff and volunteers (physicians, physician assistants, nurse practitioners, registered nurses, social workers, chaplains, administrators, and volunteers) who provide end-of-life care to patients in both home and institutional settings for 4 organizations in 2 counties in Upstate New York. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
(16 reference statements)
1
22
0
4
Order By: Relevance
“…End-of-life (EoL) care, as part of palliative care, revolves around maintaining the quality of life of patients and their families, through comprehensive management of physical symptoms, psycho-social and spiritual difficulties. End-of-life care focuses on a short period of time before death [ 2 ] and includes discussion of medical practices (suspending or withholding specific cancer treatment and general care related to feeding, hydration, and resuscitation techniques; symptom management; euthanasia) and decision-making [ 3 , 4 ]. These decisions include p alliative sedation [ 5 ] and euthanasia.…”
Section: Introductionmentioning
confidence: 99%
“…End-of-life (EoL) care, as part of palliative care, revolves around maintaining the quality of life of patients and their families, through comprehensive management of physical symptoms, psycho-social and spiritual difficulties. End-of-life care focuses on a short period of time before death [ 2 ] and includes discussion of medical practices (suspending or withholding specific cancer treatment and general care related to feeding, hydration, and resuscitation techniques; symptom management; euthanasia) and decision-making [ 3 , 4 ]. These decisions include p alliative sedation [ 5 ] and euthanasia.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that exercise, quitting smoking, limiting alcohol consumption, participating in learning activities, and integrating into society can help them to control many diseases and reduce their loss of functional capacity, which improves their quality of life and life expectancy. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have explored aspects of QOD such as adequate symptoms control, facing and understanding death with an open mind, acceptance of death, honoring of autonomy and decision rights, preparation for passing away, to be seen as a whole person, meet the choice where they want to the end, and pass away during sleep, etc 17‐21 . Most studies investigating QOD among terminally ill patients with cancer were from the perspective of patients and families, and only a few studies evaluating the influence of medical treatments on the QOD suggested that appropriate management is essential to a good QOD 19,22 . Little is known about the relationship between AH use and QOD through cross‐cultural and multi‐national research.…”
Section: Introductionmentioning
confidence: 99%